INCREASING STUDENTS LEARNING OUTCOMES IN RHYTHM PATTERNS MATERIALS THROUGH THE LET’S SING BOOK IN BANYUAJUH 2 - Cindy Amelia Mulyono; Kusnaningsih Kusnaningsih; Rika Wulandari (Citra Dharma Cindekia, 2022)
This study aims to improve the learning outcomes of class III Banyuajuh 2 Elementary School students in SBdP subjects. This type of research is Classroom Action Research. This research was conducted in 2 cycles where each cycle was carried out one class action meeting. The subjects of this study were 23 students of class III Banyuajuh 2 Elementary School in the 2022/2023 academic year. The data sources of this research are primary and secondary data sources. In the research technique used is using observation techniques, interviews, and documentation. While the data analysis used is qualitative and quantitative data analysis. The final result obtained is the total score that has been obtained by students of 1,704 with an average score of students in the first cycle of 74% of the 23 students who were given the test. the number of students 19 students have achieved increased learning outcomes and 4 students have not increased. The presentation of learning completeness obtained was 82.60%. However, these data can already show that there is an increase in student learning outcomes. In the second cycle there were several improvements, namely an increase in the number of completeness compared to the first cycle. So from that it can be said that using the lets sing book is able to improve completeness and improve learning outcomes for class III Banyuajuh 2 Elementary School.